Anti-inflammatory and chondroprotective effects of the S-adenosylhomocysteine hydrolase inhibitor 3-Deazaneplanocin A, in human articular chondrocytes - Juliette Aury-Landas (Nature Portfolio, 2017)
Abstract 3-Deazaneplanocin A (DZNep) is an inhibitor of S-Adenosyl-L-Homocysteine Hydrolase (SAHH) known to inhibit EZH2, a histone methylase upregulated during osteoarthritis. In this study, we assessed its effects in human articular chondrocytes. Anti-inflammatory effects were assessed by Nitric Oxide (NO), Prostaglandin E2 (PGE2) and Metalloprotease (MMP) release in IL-1β-stimulated chondrocytes. MAPK and NFκB activation was analyzed by western blotting. Differentially expressed genes (DEG) regulated by DZNep were identified by whole-transcriptome microarray. DZNep inhibited SAHH activity and was not toxic. It counteracted NO, PGE2 and MMP release, and reduced MAPK activation induced by IL-1β. By whole-transcriptome analysis, we identified that DNZep counteracts the effect of IL-1β on the expression of 81 protein-coding genes, including CITED2, an MMP inhibitor. These genes are organized in a protein-protein network centred on EGR1, which is known to functionally interact with EZH2. Gene ontologies enrichment analysis confirmed that DZNep counteracts IL-1β-induced expression of genes involved in cartilage matrix breakdown (MMPs and ADAMTS). In addition, DZNep up-regulated cartilage specific genes, such as COL2A1 and SOX9, suggesting a chondroprotective effect of DZNep. DZNep exhibits anti-inflammatory effects, and regulates genes implicated in chondroprotective response in human articular chondrocytes, suggesting that inhibitors of S-adenosylmethionine-dependent methyltransferases could be effective treatments for OA.